THE INFLUENCE OF VILLAGE FINANCIAL PERFORMANCE ON FINANCIAL MANAGEMENT VILLAGE IN BOGOR REGENCY - Aminda, Renea Shinta; Jiddan Aziz, Raden Muhammad; Syaukat, Yusman; Arsyianti, Dwi; Suharti, Titing (Media Ekonomi, 2024)
The research was conducted in six villages in Bogor Regency during March and April, using primary and secondary data. Secondary data was obtained from accountability reports reflecting village income and expenditure budgets from 2018 to 2022, while primary data was collected through interviews for input into process hierarchy analysis. A purposive sampling method was used to select the villages, based on location, the Village Building Index (IDM), and recommendations from the Bogor District Empowerment and Village Service. The study's independent variables included Financial Activity, Financial Growth, Financial Independence, and Financial Performance which were calculated using ratios, while the dependent variable was Financial Management. The data was analyzed using quantitative descriptive analysis, village financial ratio analysis, and panel data regression tests, combining time series and cross-sectional data. This study uses villages as sample objects by assessing financial performance through village independence, village financial activities, and village financial growth towards efficiency in Bogor Regency in March and April. The data used include primary data obtained from accountability reports detailing the realization of village revenue and expenditure budgets from 2018 to 2022 and secondary data. The analysis methods used include descriptive statistics, financial ratio analysis, and panel data regression. The currently available resources result in a limited Regional Original Revenue (PAD) generation. The socio-economic status of the village residents remains modest, and the supply of huge transfer income makes the village dependent on assistance. In financial activities, namely operations, it is still considered low. This is because the needs of the village are still small, with a low population, and an emphasis on capital spending as the main focus of the village. According to the applicable policies, the targets for priority use of Village Funds, Village Fund Allocations, Share of Regional Tax and Levy Proceeds, and Provincial/Regency Financial Assistance are to be achieved.